IMPACT OF COVID-19 LOCKDOWN ON NO2, NOX, O3 AND PM2,5 CONCENTRATIONS IN SANTIAGO DE CHILE - Sonnia Parra Vargas; Manuel Bravo (Journal of the Chilean Chemical Society, 2021)
Based on the spread of the COVID-2019, a lockdown was declared in the Santiago Metropolitan area in Chile.  The application of containment measures allowed to reduce the impact of the COVID-2019 pandemic on the National Health System (MINSAL) but at the same time these restriction measures gave also the opportunity to assess the effect of anthropogenic activities on air pollutants. A comparative study of typical behavior of atmospheric pollutants O3, NO2, NOx and PM2.5 during the years 2015-2020 are presented.For the eight studied stations (Las Condes, Pudahuel, El Bosque, Cerro Navia, La Florida, Independencia, Parque O`Higgins and Puente Alto) it was possible to determine the seasonal variation of NO2, NOx, O3 and PM2.5.As results of impact of the lockdown, in this paper we have been determined a significant reduction of pollutants concentration mainly due to vehicular traffic.